Migration and trapping of the Ionian series hydrocarbons (Epirus, NW Greece) - KARAKITSIOS, V.; RIGAKIS, N.; BAKOPOULOS, I. (Bulletin of the Geological Society of Greece, 2001)
Surface oil shows in the Ionian zone of NW Greece are mainly linked to the organic matter rich Lower Posidonia beds of Toarcian age and shale fragments within the Triassic breccias. The calcareous formations of the Ionian series are characterized by insignificant primary porosity-permeability. Only fractured carbonates might comprise potential reservoir rocks capped on top by the detrital series. Other prospective traps, with the evaporites playing the role of cap-rocks, are related to the degree of basement involvement in the structural evolution of the Ionian basin.